Socially important infectious diseases posing a biological threat to the population of Russia - O. B. Nechaeva (Туберкулез и болезни лёгких)
The objective: to determine the status and prospects of medical care provision for socially important infectious diseases that pose a biological threat to the population of Russia. Subjects and methods. Data from FGSN forms no. 4, 8, 12, 14, 14 DS, 30, 33, 47, 61 were analyzed. The number of those died is presented as per the data of Rosstat. Research methods: epidemiological and statistical analysis, expert assessment, content analysis of publications and regulations. Results. For diseases that pose a biological threat to the population (tuberculosis, HIV infection, viral hepatitis B and C), various epidemiological trends are currently observed: improved situation with tuberculosis and acute viral hepatitis B and C, stabilization with a tendency to improve in hronic viral hepatitis B and C, and stabilization in HIV infection situation. At employable age, diseases representing a biological threat to the population and their combination as causes of death in 2018 were registered in 9.2% of those died (excluding the cause of death from external causes). Monitoring of HIV incidence and HIV mortality in the Russian Federation and activities aimed at preventing the transmission of the disease caused by HIV, as well as viral hepatitis B and C, requires improvement. There are no FGSN forms on viral hepatitis; FGSN forms on HIV infection are to be improved. There are no registration forms for notification of HIV infection and viral hepatitis B and C cases. As a result, the indicators calculated based on data from FGSN forms and Rospotrebnadzor differ. Thus, there are no reliable data on the incidence and prevalence of HIV infection, viral hepatitis B and C.Due to a significant decrease in tuberculosis incidence resulting from changes in the socio-economic situation in the country and properly organized work in tuberculosis care provision to the population, at present, the number of contingents of tuberculosis medical organizations does not allow closing the visit plan for TB doctors in outpatient settings and fulfilling work standards for beds in in-patient TB units. Properly organized TB service, able to work with different units and services, can help to provide medical care to patients infected with HIV and hepatitis B and C. Setting up medical units such as Centers for Socially Important Infectious Diseases in the regions of the Russian Federation using the facilities of TB services and AIDS centers can help in the organization of control over diseases that pose a biological threat to the population of this country.